2017
DOI: 10.1002/2017jd026690
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Urban Heating and Local Winds During the Calm Intermonsoon Seasons in the Tropics

Abstract: Rapid urbanization of cities has greatly modified the thermal and dynamic profile in the urban boundary layer. This paper attempts to study the interaction of urban heating and the local topographic‐induced flow circulation for a tropical coastal city, Greater Kuala Lumpur, in Malaysia. The role of sea‐and‐valley‐breeze‐orientated synoptic flow (SBOS) on the interaction is determined by comparing two intermonsoon periods. A state‐of‐the‐art numerical model, Advanced Research Weather Research and Forecasting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 94 publications
2
20
0
Order By: Relevance
“…By 17:00 LT (not shown) the boundary layer height is highly variable and the 304 K air mass is well aloft at 1,100 to 1,200 m. The surface air temperature has cooled to ~300 K. The heat island circulations are starting to mature during this time (Figure c), and the sea breeze is prevented from moving further inland after it reaches the catchment area due to the interaction of the heat island circulation and the sea breeze. The patterns of sea breeze for the Control case are found similar to that reported by Ooi et al () in Malaysia.…”
Section: Resultssupporting
confidence: 87%
“…By 17:00 LT (not shown) the boundary layer height is highly variable and the 304 K air mass is well aloft at 1,100 to 1,200 m. The surface air temperature has cooled to ~300 K. The heat island circulations are starting to mature during this time (Figure c), and the sea breeze is prevented from moving further inland after it reaches the catchment area due to the interaction of the heat island circulation and the sea breeze. The patterns of sea breeze for the Control case are found similar to that reported by Ooi et al () in Malaysia.…”
Section: Resultssupporting
confidence: 87%
“…Monsoon season (boreal summer monsoon between May and September; see Ooi et al 2017b), followed a precipitation incident the previous evening. This particular day was chosen for analysis because of the availability of satellite imagery with minimum cloud cover.…”
Section: City Scale Urban Climate Modelling Of Greater Kuala Lumpur Bmentioning
confidence: 99%
“…Kuala Lumpur (3°09ʹ35ʺN 101°42ʹ 00ʺE) is located in the tropics, and has two distinct monsoon seasons, i.e. the relatively drier Southwest Monsoon from May to September, and the rainy Northeast Monsoon from November to March (Ooi et al 2017b). On course to be a world class city, Kuala Lumpur will continue its development in the next decade.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies found that urbanization strengthened the sea breezes, significantly increasing precipitation. Numerical studies for coastal cities adjacent to mountains have been also done, for instance, for the cities of Taipei, Taiwan (e.g., Lin et al, 2008Lin et al, , 2011, Taichung, Taiwan (e.g., Lin et al, 2008), Guangzhou, China (e.g., Wang et al, 2014), Kuala Lumpur, Malaysia (e.g., Argüeso et al, 2016;Ooi et al, 2017), São Paulo, Brazil (e.g., Vemado and Pereira Filho, 2016) and Tokyo, Japan (Matheson and Ashie, 2008;Shimoju et al, 2010;Inamura et al, 2011;Souma et al, 2013;Kusaka et al, 2014;Seino et al, 2016Seino et al, , 2018Bélair et al, 2018). Lin et al (2008) showed that the interaction of the UHI effect with sea breezes and mountain uplift increase rainfall in the mountainous areas on the leeward sides of Taipei and Taichung.…”
Section: Introductionmentioning
confidence: 99%